2018
DOI: 10.1177/1524500418766355
|View full text |Cite
|
Sign up to set email alerts
|

Developing the UNICEF Malawi School Handwashing Program

Abstract: Diarrhea is one of the major causes of morbidity and mortality among children and immune-compromised individuals in Malawi. Handwashing with soap (HWWS) is one of the most cost-effective health interventions to prevent diarrhea. United Nations Children’s Fund (UNICEF) Malawi has adopted a social marketing approach to achieve large-scale behavioral change for HWWS. The study, commissioned by UNICEF Malawi, was developed by PSI Malawi and Griffith University and conducted by PSI Malawi. Formative research insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…However, so far only a few studies analyzed domestic handwashing on the basis of SEMs. In a study in Malawi, an SEM was used to develop a handwashing program for schools [ 24 ]. The researchers found that handwashing was not supported at the community level, which resulted in reluctance among the students to wash their hands and regular theft of handwashing supplies as soon as new equipment was bought.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far only a few studies analyzed domestic handwashing on the basis of SEMs. In a study in Malawi, an SEM was used to develop a handwashing program for schools [ 24 ]. The researchers found that handwashing was not supported at the community level, which resulted in reluctance among the students to wash their hands and regular theft of handwashing supplies as soon as new equipment was bought.…”
Section: Introductionmentioning
confidence: 99%
“…Notably three of the four current practice studies that used observation to identify handwashing practices had relatively small sample sizes of between one and six schools (Pete 1986;Guinan et al 1997;Xuan & Hoat 2013). Fifteen (88%) of the studies used just one tool, with twelve only using self-report (Lopez-Quintero et al 2009;Setyautami et al 2012;Sibiya & Gumbo 2013;Peltzer & Pengpid 2014;Azuogu et al 2016;Ranasinghe et al 2016;Susanto et al 2016;Tamilarasi et al 2016;ALBashtawy 2017;Seimetz et al 2017;Thakadu et al 2018) and three only observation (Pete 1986;Guinan et al 1997;Parkinson et al 2018). Two studies also supported self-report with either observation (Xuan & Hoat 2013) or detection tests (Grimason et al 2014).…”
Section: Current Practicementioning
confidence: 99%
“…• Observation was used to measure (i) in twenty-one studies occurrence, frequency and /or quality of handwashing to indicate behaviour (Pete 1986;Day et al 1993;Guinan et al 1997;Early et al 1998;O'Reilly et al 2008;Snow et al 2008;Blanton et al 2010;Graves et al 2012;Patel et al 2012;Bieri et al 2013;Pickering et al 2013;Xuan & Hoat 2013;Caruso et al 2014;Pickering et al 2014;Lee et al 2015;Mohamed Moussa et al 2015;Dreibelbis et al 2016;La Con et al 2017;Solehati et al 2017;Chard & Freeman 2018;Grover et al 2018;Parkinson et al 2018), (ii) in two studies illness prevalence manifest in absence (Caruso et al 2014;Chard & Freeman 2018) and in two studies sickness (Bowen et al 2007;Pickering et al 2013) to indicate a health outcome.…”
Section: Measurement Toolsmentioning
confidence: 99%
“…In Myanmar, one study mentioned that household visits by local authorities had a significant influence on the adoption of handwashing practices after defecation [ 21 ]. In a broader sense, the designation of a handwash champion in Bangladesh and Malawi could take the form of a schoolteacher or a compound manager whose objective was to engage the students and community members to foster a good hand hygiene environment by encouraging them to wash their hands at key times and replenish the soapy water supply [ 16 , 18 , 22 ].…”
Section: Theoretical Domains Framework (Tdf)mentioning
confidence: 99%
“…Five out of 46 studies identified the intention not to wash hands as a barrier to hand hygiene. The unwillingness to practice handwashing was cited in three studies in which inhabitants of camps in the Democratic Republic of the Congo were unwilling to subscribe to hygiene mandates, and students in Malawi and Vietnam were reluctant to handwash because of the lack of support from teachers and family [ 19 , 22 , 23 ]. Two other studies reported that in Bangladesh and Mali, being too busy acted as a barrier to maintaining handwashing stations and washing hands because of heavy workloads in the form of household or laborious jobs [ 34 , 35 ].…”
Section: Theoretical Domains Framework (Tdf)mentioning
confidence: 99%